SBSN Financing and Infrastructure Performance in Islamic Higher Education - Muhtadin; Athok Fuadi; Lukman Hakim (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2026)
Government-issued State Sharia Securities (SBSN) have become an increasingly important funding source for infrastructure development in Indonesian Islamic universities. However, the performance of SBSN-funded projects often varies, raising concerns regarding governance, planning quality, and stakeholder engagement. This study aims to model the key determinants of project performance in SBSN-funded Islamic university infrastructure programs using a PLS-SEM approach. The object of this study is the Kiai Ageng Muhammad Besari State Islamic University (UIN) in Ponorogo. A total of 165 project stakeholders at the University participated in a structured survey based on five constructs: Project Planning Quality, Managerial Capability, Monitoring and Evaluation System, Stakeholder Engagement, and Project Performance. The results show that Managerial Capability has the strongest direct influence on project performance. Stakeholder Engagement and Monitoring and Evaluation also show significant influences. Interestingly, Project Planning Quality does not have a significant direct influence on monitoring or performance, but contributes indirectly through managerial and evaluative channels. These findings underscore the importance of integrating planning with leadership, institutional monitoring, and participatory mechanisms to achieve optimal project outcomes. This study contributes to the development of a governance model for religious finance-based infrastructure programs and provides practical insights for universities and policymakers to improve SBSN implementation. Future research could explore longitudinal changes, regulatory factors, and digital tools in infrastructure governance. Abstrak Surat Berharga Syariah Negara (SBSN) yang diterbitkan pemerintah telah menjadi sumber pendanaan yang semakin penting untuk pengembangan infrastruktur di Perguruan tinggi keislaman Indonesia. Namun, kinerja proyek yang didanai SBSN seringkali bervariasi, sehingga menimbulkan kekhawatiran terkait tata kelola, kualitas perencanaan, dan keterlibatan pemangku kepentingan. Studi ini bertujuan untuk memodelkan penentu utama kinerja proyek dalam program infrastruktur universitas Islam yang didanai SBSN menggunakan pendekatan PLS-SEM. Objek Penelitian ini adalah Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo. Sebanyak 165 pemangku kepentingan proyek di Universitas UIN Kiai Ageng Muhammad Besari Ponorogo berpartisipasi dalam survei terstruktur berdasarkan lima konstruk: Kualitas Perencanaan Proyek, Kemampuan Manajerial, Sistem Pemantauan dan Evaluasi, Keterlibatan Pemangku Kepentingan, dan Kinerja Proyek. Hasil penelitian menunjukkan bahwa Kemampuan Manajerial memiliki pengaruh langsung terkuat terhadap kinerja proyek. Sedangkan Keterlibatan Pemangku Kepentingan dan Pemantauan dan Evaluasi juga menunjukkan pengaruh yang signifikan. Menariknya, Kualitas Perencanaan Proyek tidak memiliki pengaruh langsung yang signifikan terhadap pemantauan maupun kinerja, tetapi berkontribusi secara tidak langsung melalui jalur manajerial dan evaluatif. Temuan ini menggarisbawahi pentingnya mengintegrasikan perencanaan dengan kepemimpinan, pemantauan kelembagaan, dan mekanisme partisipatif untuk mencapai hasil proyek yang optimal. Studi ini berkontribusi pada pengembangan model tata kelola untuk program infrastruktur berbasis keuangan keagamaan dan memberikan wawasan praktis bagi universitas dan pembuat kebijakan untuk meningkatkan implementasi SBSN. Penelitian selanjutnya dapat mengeksplorasi perubahan longitudinal, faktor regulasi, dan alat digital dalam tata kelola infrastruktur.